Kepemimpinan Spiritual dan Reward Terhadap Kinerja Pegawai Melalui Kualitas Kehidupan Kerja Dan Kepuasan Kerja sebagai Variabel Intervening - Padmayuda Tri Rachmawan; Dwi Nita Aryani (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2020)
The purpose of this study is to analyze the influence spiritual leadership and reward toward employee performance with quality of work life and job satisfaction as mediating variable. The object of research in this study is Pasuruan Regency Transportation Office. Data analysis uses the Partial Least Square method with the software of SmartPLS. Data is collected by distibuting questionnaire to all of 86 staff as the respondents. The results show Spiritual leadership does not affect the employee performance; reward has no effect on employee performance; Spiritual leadership does not affect employee performance mediated by the quality of work life; Reward cannot influence employee performance through the quality of work life as a mediating variable; Spiritual leadership does not have an effect on employee performance which is mediated by quality of work life; the indirect effect between reward on employee performance through mediating job satisfaction is significant; The quality of work life has insignificant effect on employee performance; Job satisfaction has a positive and significant effect on employee performance. The results give significant implications on practice and literature on the influence of spiritual leadership and reward on performance. This research provides information that can be used as a guideline for the Pasuruan Communication Office to increase employee satisfaction and performance